Monte Carlo renormalization group with evolution in the space of parameters - Caticha, Nestor; Chahine, Jorge [UNESP]; Felicio, José Roberto Drugowich de (American Physical Society, 1989)
Using data from a single simulation we obtain Monte Carlo renormalization-group information in a finite region of parameter space by adapting the Ferrenberg-Swendsen histogram method. Several quantities are calculated in the two-dimensional N 2 Ashkin-Teller and Ising models to show the feasibility of the method. We show renormalization-group Hamiltonian flows and critical-point location by matching of correlations by doing just two simulations at a single temperature in lattices of different sizes to partially eliminate finite-size effects.